Numerical study on the impact of water-rock interactions on the propagation of water-flooding induced fracture - Qu, Hongyan; Peng, Yan; Pan, Zhejun; Xu, Xiangdong; Zhou, Fujian (Frontiers in Earth Science, 2023)
Water-flooding is an effective way to develop the extra-low permeability oil reservoirs and the water-flooding induced fracture (WIF) can improve waterflooding efficiency. However, geomechanical properties of rocks may alter due to the water-rock interactions, which usually increases the heterogeneity of reservoir properties and affects the WIF propagation. In this study, a method to calculate the WIF propagation length was proposed and numerical models were established considering the effect of water-rock interactions on geomechanical properties. In addition, the numerical model of stress distribution of the WIF propagation was validated by theoretical solutions based on the fracture mechanics. Moreover, the WIF propagation mechanism and the effect of water-rock interactions on the WIF propagation was analyzed. Results indicate that the numerical model is valid to calculate the stress distribution induced by the WIF with an error under 5%. In addition, the WIF propagation can be affected by several factors, including the injection pressure, the damage variable and the initial fracture length. Noteworthy, the injection pressure should be strictly controlled because the WIF propagation is highly sensitive to the injection pressure. An increase of 2 MPa in the injection pressure can result in 90m WIF propagation length, accounting for 64% of initial fracture length in the case studied in this work. Moreover, water-rock interactions aggravate the heterogeneity of the reservoir and promote the WIF propagation due to the alteration of the geomechanical properties such as Young’s modulus. Therefore, the WIF can propagate even if the injection pressure is less than the minimum horizontal stress. Furthermore, the stress intensity factor (KIA) and WIF propagation length increase with the initial fracture length, which may lead to sudden water flux and reduce the efficiency of waterflooding.